Anti-Violence Education Against Children - Yulianingsih, Yuyun (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2016)
This article aimed to analyze the anti-violence education to early childhood in Islamic perspective. Documentation is used as data collection method in this research. And critical analysis is used as data analysis technique. By this method, the research finds that: (1) violence against children occurs because of lack of understanding about what is exactly the characteristic of early chilhood. (2) Islam has explained the rights and protection of children (3) understanding the characteristic of the children is one of the core of anti-violence education against children. Keywords: Education, Violence, Child, Islam. Artikel ini bertujuan untuk menganalisis pendidikan anti kekerasan terhadap anak usia dini dalam perspektif Islam. Metode pengumpulan data yang digunakan ialah studi dokumentasi. Teknik analisis data yang digunakan ialah analisis kritis. Berdasarkan metode tersebut, diperoleh temuan penelitian bahwa: (1) kekerasan terhadap anak terjadi akibat rendahnya pemahaman tentang anak sejak usia dini. (2) Islam telah menjelaskan hak dan perlindungan terhadap anak (3) pemahaman mengenai kondisi anak merupakan salah satu inti pendidikan anti kekerasan teradap anak. Kata kunci: Pendidikan, Kekerasan, Anak, Islam.